2009
DOI: 10.1111/j.1538-7836.2008.03248.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated factor XII type A predicts long‐term mortality in patients admitted with chest pain

Abstract: , XIIaA provided independent prognostic information for all-cause mortality (HR 3.88; 95% CI, 1.66-9.08) and for the combined endpoint of death or recurrent TnT positive event (HR 2.46; 95% CI, 1.34-4.50). Conclusion: XIIaA, a recently identified in vivo form of activated factor XII is an independent indicator of long-term all-cause mortality in patients admitted with chest pain, providing prognostic information above and beyond conventional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…This in-vivo XIIa can be further categorized on the basis of its availability to react with specific antibodies, in which XIIaA represents the XIIa that is readily available to bind with antibodies and XIIaR requires the addition of supplementary reagents (such as Triton-X100; J T Baker Inc., Phillipsburg, New Jersey, USA) to release the XIIa from binding partners and enable detection using the specific antibodies. We have demonstrated that one of these recently discovered forms of XIIa, termed XIIaA, predicts longterm mortality in an ACS population, independently of BNP [12]. Interestingly, the outcome prediction was most pronounced in patients with low or absent troponin release and weakest for patients with higher admission troponins, which differed from our findings with BNP for which the most powerful predictive value was obtained in chest pain patients with troponin T (TnT) values above 0.05 ng/ml.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…This in-vivo XIIa can be further categorized on the basis of its availability to react with specific antibodies, in which XIIaA represents the XIIa that is readily available to bind with antibodies and XIIaR requires the addition of supplementary reagents (such as Triton-X100; J T Baker Inc., Phillipsburg, New Jersey, USA) to release the XIIa from binding partners and enable detection using the specific antibodies. We have demonstrated that one of these recently discovered forms of XIIa, termed XIIaA, predicts longterm mortality in an ACS population, independently of BNP [12]. Interestingly, the outcome prediction was most pronounced in patients with low or absent troponin release and weakest for patients with higher admission troponins, which differed from our findings with BNP for which the most powerful predictive value was obtained in chest pain patients with troponin T (TnT) values above 0.05 ng/ml.…”
Section: Introductionmentioning
confidence: 64%
“…The details of the baseline characteristics of the total patient population and unadjusted hazard ratios for the different endpoints within 2 years for XIIaA and BNP have been reported previously [12]. Baseline characteristics for the subgroups classified according to their peak 654 Blood Coagulation and Fibrinolysis 2009, Vol 20 No 8 Table 1 Baseline characteristics for patient strata divided for subgroups according to peak troponin T release following admission TnT level at admission are displayed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Grundt et al [42] identified an association between the highest quartile of FXIIa among patients surviving a myocardial infarction and future ACS. Similarly, Ponitz et al [43] reported that FXIIa was an independent predictor of allcause mortality among patients with ACS. Interestingly, a large Viennese patient study (n=8936) showed that all-cause mortality of patients severely deficient in FXII (<10%) was similar to that of patients with normal FXII plasma levels, suggesting that severe deficiency and normal plasma levels both offer the same degree of thromboprotection [44].…”
Section: Factor XII and Thrombosis Phenotypesmentioning
confidence: 96%
“…Significant positive relationships between plasma FXIIa concentrations and BP [12,13] and an inverse relationship between glomerular filtration rate and FXIIa [14] have been reported. Patients with end-stage renal disease (ESRD) exhibit up to 10-fold increases in plasma FXIIa concentrations [15][16][17].…”
Section: Introductionmentioning
confidence: 92%